THE EVALUATION IN UNIVERSITIES OF PHYSICAL EDUCATION AND SPORT - Constantin Ciorbă (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
This work is dedicated to the problems of optimization of the Universities of Physical Education and Sport by means of the elaboration of evaluation.